Layanan Dukungan Psikososial bagi Korban Bencan - Raihan Rahman Hidayat; Rohmat Efendi; Yayu Fitri Balqis. S (Sultan Idris Journal of Psychology and Education, 2025)
Disasters cause damage to the function of society, material, economy, and environment. This study aims to determine the right intervention given to individuals to overcome psychological problems, especially groups most affected by disasters. Children are the next generation of the nation, psychological trauma will hinder children's ability to grow and develop well both mentally and physically. The form of intervention that can be done is psychosocial support services (LDP), LDP aims to improve children's social functioning through play therapy and provide an understanding of clean and healthy living behavior (PHBS) in children after a disaster.